Phase II randomised discontinuation trial of cabozantinib in patients with advanced solid tumours. (November 2017) - Schöffski, Patrick; Gordon, Michael; Smith, David C.; Kurzrock, Razelle; Daud, Adil; Vogelzang, Nicholas J.; Lee, Yihua; Scheffold, Christian; Shapiro, Geoffrey I.
Abstract: Background: Cabozantinib is an inhibitor of tyrosine kinases, including MET,  vascular endothelial growth factor receptor, AXL and RET. This multi-cohort phase II randomised discontinuation trial explored anticancer activity of cabozantinib in nine tumour types. Patients and methods: Cabozantinib was administered (100 mg, once daily) to patients with advanced, recurrent or metastatic cancers. Those with stable disease at week 12 were randomised 1:1 to cabozantinib or placebo. Primary end-points were objective response rate (ORR) at week 12 and progression-free survival (PFS) in the randomised phase. Results: A total of 526 patients were enrolled. The highest ORR was observed in ovarian cancer (OC) (21.7%); the largest PFS benefit was observed in castration-resistant prostate cancer (CRPC) (median 5.5 versus 1.4 months for placebo; hazard ratio 0.14, 95% confidence interval: 0.04, 0.52). Disease control rates were >40% for CRPC, OC, melanoma, metastatic breast cancer (MBC), hepatocellular carcinoma (HCC) and non–small cell lung cancer. Median duration of response ranged from 3.3 (MBC) to 11.2 months (OC). Encouraging efficacy results and symptomatic improvements prompted early suspension of the randomised stage and conversion to open-label non-randomised expansion cohorts. Dose reductions to manage adverse events (AEs) occurred in 48.7% of patients. The most frequent grade III–IV AEs were fatigue (12.4%), diarrhoea (10.5%), hypertension (10.5%) and palmar-plantar erythrodysesthesia syndrome (8.7%). Conclusions: Clinical antitumour activity of cabozantinib was observed in a subset of tumour types: CRPC and OC were evaluated further in expansion cohorts. Phase III programs were initiated in CRPC and HCC. Interpretation of efficacy outcomes was limited by early termination of the randomised portion of the trial. Trial registration number: NCT00940225 . Highlights: Cabozantinib was evaluated in a phase II randomised discontinuation trial (RDT). Cabozantinib demonstrated antitumour activity in multiple solid-tumour types. Results from this RDT supported initiation of phase III programs in castration-resistant prostate cancer and hepatocellular carcinoma.